Genomic structural variation-mediated allelic suppression causes hybrid male sterility in rice. Issue 1 (December 2017) - Shen, Rongxin; Wang, Lan; Liu, Xupeng; Wu, Jiang; Jin, Weiwei; Zhao, Xiucai; Xie, Xianrong; Zhu, Qinlong; Tang, Huiwu; Li, Qing; Chen, Letian; Liu, Yao-Guang
Abstract Hybrids between divergent populations commonly show hybrid sterility; this reproductive barrier hinders hybrid breeding of thejaponica andindica rice (Oryza sativa L.) subspecies. Here we show that structural changes and copy number variation at theSc locus conferjaponica–indica hybrid male sterility. Thejaponica allele, Sc-j, contains a pollen-essential gene encoding a DUF1618-domain protein; theindica allele, Sc-i, contains two or three tandem-duplicated 28-kb segments, each carrying anSc-j -homolog with a distinct promoter. InSc-j /Sc-i hybrids, the high-expression ofSc-i in sporophytic cells causes suppression ofSc-j expression in pollen and selective abortion ofSc-j -pollen, leading to transmission ratio distortion. Knocking out one or two of the threeSc-i copies by CRISPR/Cas9 rescuesSc-j expression and male fertility. Our results reveal the gene dosage-dependent allelic suppression as a mechanism of hybrid incompatibility, and provide an effective approach to overcome the reproductive barrier for hybrid breeding. A reproductive barrier betweenjaponica andindica rice subspecies hinders hybrid breeding. Here, the authors reveal that structural and copy number variations of a pollen-essential gene, which encodes a DUF1618-domain protein, result in allelic suppression and subsequently cause hybrid male sterility.